# algebra

posted by .

2 (x-3)-3(x+5) = 3(x-2) -7

distributive property
2x -6 -3x -15 = 3x -6 -7
combine like terms
-x -21 = 3x -13

add x and 13 to both sides

-7 = 4x

multiply both sides by 1/4

-7/4 = x

## Similar Questions

1. ### Variable

SOLVING EQUATIONS WITH THE VARIABLE ON BOTH SIDES Solve the equation. Then check your solution. 4x-9 = 7x+12 Just remember that one can add, subtract, multiply, divide, etc but whatever is done to one side must be done to the other …

3. ### Algerbra 1

1/3x + 5/6 = 2/9x - 1/3 How do I solve this to get the answer?
4. ### math

5n-34>7(n-2) You might start by using the distributive property on the right hand side to get 7n-14, then subtact the 5n from both sides and add 14 to both sides.
5. ### algebra--distributive

how would you do this prob. negative4-(5y+6) = negative 7y+3 thanks. happy halloween I'm going to assume your problem is this: -4 - (5y + 6) = -7y + 3 If that's the case, distribute the negative over the terms in the parentheses first: …
6. ### Maths

you have to solve the following by finding the value of x and y. can u help please?
7. ### Algebra

Solve S=a/(1-r) for r S = a/(1-r) Multiply both sides by 1-r S*(1-r) = [(1-r)*a]/(1-r) Simplify S*(1-r) = a Multiply terms on the left. S - S*r = a Subtract S from both sides. S-S*r - S = a - S Simplify -S*r = a - S Multiply both sides …
8. ### Algebra

89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, and this is the reply I got from someone: multiply both sides by 7 6x-42=-14 add 42 to each side 6x=28 x=14/3 But I don't get how this is done because to eliminate …
9. ### Geometry

Given: 7x + 2 = 2 + 5x – 6 Prove: x = –3 Given the equation 7x + 2 = 2 + 5x – 6, use the commutative property to rearrange the terms so that like terms are next to one another. This gives the equation 7x + 2 = 2 – 6 + 5x. Then, …
10. ### Algebra

Which of the following describes a correct method for solving the equation below?

More Similar Questions